069 Facilitating Implementation of Guidelines for the Prevention of Vascular Disease In General Practice. (15th August 2013) - Harris, M; Litt, J; Russell, G; Mazza, D; Lloyd, J; Zwar, N; Taylor, R; Driel, M Van; Mar, C Del; Krastev, Y; Parker, S; Smith, J
Abstract : Background: Although evidence based guidelines have been developed and disseminated, up to a half of patients do not receive guideline based preventive care. Objectives: This study aims to evaluate a model for the implementation of preventive care guidelines in general practice. Methods: Following a development process for the intervention involving a mixed method study and a pilot carried out in three practices a cluster randomised controlled trial is being conducted in 31 practices across four states. The intervention involves training, preventive care audit, and visits from a facilitator based in the local primary care support organisation. The facilitator assists practices to review their clinical audit and implement a practice plan structured around the 5As to improve the reach and quality of preventive care. Quantitative and qualitative evaluation methods are being used to assess impact on planned change within the practice, recalled and recorded preventive care, and patient behaviours and risk factors for cardiovascular disease. Results: Baseline data collection has been completed from practice staff and patients and the intervention is now complete. The recorded and patient recalled preventive care varied within and between practices resulting in a varied set of priorities for improvement. Early findings suggest that facilitation visits to review and plan improvements to the implementation of preventive guidelines are feasible, acceptable and can support organisational strategies to address gaps in care. Discussion: Our results may provide a model for local primary care support organisations to assist practices to improve their quality of preventive care.